The Influence of Madrasah Principal’s Leadership, Teacher’s Learning Media, and Teacher’s Teaching Style on Student’s Learning Achievement - Prabowo, Wendi; Fitria, Happy; Wahidy, Achmad (JMKSP (Jurnal Manajemen, Kepemimpinan, dan Supervisi Pendidikan), 2024)
This study aims to examine the influence of Madrasah Principal Leadership, Teacher Learning Media, and Teaching Styles on Student Achievement at Madrasah Aliyah in Banyuasin III District. In this study, quantitative methods were used as research methods. The sampling technique was purposive sampling. Data was collected by distributing questionnaires using a 5-point Likert scale to measure 80 statement items. This study shows that 1) the leadership of the madrasa principal has a partial and significant effect on student learning achievement with a t-count value > from t table or 7.721> 1.9839 2) Learning media has a partial and significant effect on student learning achievement with a t-count value > from t table or 21.753 > 1.9839 3) the teaching style of the teacher has a partial and significant effect on student learning achievement with a t count value > from t table or 12,247 > 1.9839 and 4) simultaneously the leadership of the madrasa principal, learning media and teacher teaching style has a positive and significant effect on student achievement with a significance level of 0.00 <0.05 with f count 166.575 > f table 2.70